Dekonstruksi Pemadanan Verba Berdiatesis Aktif Bahasa Jerman dalam Novel Bahasa Indonesia - Lukiyanti, Ira; Hariri, Tatang (Kajian Linguistik dan Sastra, 2025)
This translation research is a process of proving deconstructions as implications and negotiations oflinguistics and culture committed by a translator. Through a descriptive-qualitative approach withadvanced comparative and interpretive methods, this study investigated deconstructions of equivalencein voice verbs of the German language in Indonesian novels across eras, namely the first translated novelin 1978 and the second one in 1991. Different translators in other eras translated both novels. The dataof this study are declarative sentences that have active voices in the German language and werecollected through the note-taking technique and sampling. Based on Derrida’s theory, that language isnot constant, and Mona Baker’s translation theory, the collected data were analyzed. The result of thisstudy indicated that translation deconstructions in TSu (source text) occurred in TSa1 (target text or the1st translations) and TSa2(target text or the 2nd translations of another era). The deconstructions covered3 (three) levels: these are at word-form levels, meaning levels, and information structure levels. Thoselevels were elaborated in gaining the meaning equivalence. At the word-form level were obtained verbsof active voices of the German language were obtained in the form (i) basic verbs, (ii) verbs with prefixes,dan (iii) verb blends. These forms are then translated into (1) verbs with a variety of forms, (2) affixednouns, (3) word groups, and (4) modality, aspectuality, and grammatical function. At the meaning levelwere found active meanings and passive meanings containing propositional meanings, expressivemeanings, evoked meanings, and metaphorical meanings. At the last levels, outlined variations of theinformation structures in target languages through tematisation.